Literacy 2.0 : preparing digitally wise teachers - Coutinho, Clara Pereira (2009)
In this paper we present an experience with teachers that used Web 2.0 technologies to develop digital skills and integrate technologies in the curriculum. The theoretical framework sustains the importance of developing technological-pedagogical-content knowledge (TPACK) if we want teachers to use technologies in the classrooms. Recent research shows that teachers´ familiarity, confidence and skills in integrating technology into the curriculum are dependent on the type of education programs teachers attend. 21st century citizens need being able to read and write multiple forms of media and integrating them into a meaningful whole: this is the new hallmark of literacy 2.0 that has to be learned in the school classroom. Aware of this context and responsible for preparing digitally wise teachers we implemented a program with in-service teachers using Web 2.0 tools - blogs, podcasts and GoogleSites. Education programs must prepare teachers´ to use technologies in the classroom as cognitive tools that enhance students´ learning. For that to happen, teachers must feel at ease to handle technologies in order to design activities that motivate and engage learners in constructivist learning activities. In this article we describe and evaluate the training experience, reflect on the results and discuss guidelines for further research.